Palliative treatment of malignant ascites: profile of catumaxomab - Ammouri, Lila (Dove Medical Press, 2010)
Malignant ascites is the abnormal accumulation of fluid in the peritoneal cavity associated with several intrapelvic and intra-abdominal malignancies. The development of ascites leads to significant symptoms and poor quality of life for the cancer patient. Available therapies for palliation include treatment of the underlying disease, but when there are no treatment options, the use of diuretics, implantation of drainage catheters, and surgical shunting techniques are considered. None of these symptom palliation options affect the course of disease. The development of trifunctional antibodies, which attach to specific overexpressed surface markers on tumor cells, and trigger an immune response leading to cytoreductive effects, represents a new approach to the management of malignant ascites. The purpose of this review is to highlight current therapies for malignant ascites and review data as to the effectiveness of a new trifunctional antibody, catumaxomab.